Methylene Violet 3 RAX Dye as a New Reagent for the Determination of Nitrite in Cured Meats and Vegetables - Rocha, Caroline O. da [UNESP]; Petruci, Joao Flavio S. [UNESP]; Cardoso, Arnaldo A. [UNESP] (Soc Brasileira Quimica, 2017)
In this contribution we propose, for the first time, the use of Methylene Violet 3 RAX dye for the detection and determination of nitrite in cured meats and vegetables. Quantification is based on the decrease in absorbance of the dye, which is proportional to the nitrite concentration. The proposed method presents linear response (r > 0.99) in the range from 1.8 to 9 mu mol L-1 of nitrite, with a limit of detection of 0.14 mu mol L-1. Satisfactory accuracy with the official Association of Official Agricultural Chemists (AOAC) method was achieved, and the method was successfully applied to a wide range of cured meats and vegetables. The proposed method offers similar or superior performance to other optical methods used for the determination of nitrite in different matrices, with advantage in terms of reduction of chemical waste for each analysis, by minimizing amounts of reagents and products.
Keywords: nitrite; food analysis; cured meat; spectrophotometry; Methylene Violet 3RAX